New enzymatically polymerized copolymers from 4-tert-butylphenol and 4-ferrocenylphenol and their modification and inclusion complexes with β-cyclodextrin - Mondrzyk, Adam; Mondrzik, Beate; Gingter, Sabrina; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2012)
The enzymatically catalyzed synthesis of a copolymer of 4-tert-butylphenol and 4-ferrocenylphenol by horse radish peroxidase (HRP) in the presence of H2O2 in a 1,4-dioxane/water system is described. Furthermore, polymer-analogous alkylation of the free hydroxy groups and subsequent click reaction with mono-6-azido-6-desoxy-β-cyclodextrin (N3-β-CD) was carried out. The formation of inter- and intramolecular inclusion complexes was investigated by DLS measurement.
Keywords: copolymer; ß-cyclodextrin; enzymatic polymerization; 4-ferrocenylphenol; polyphenol; 4-tert-butylphenol; horseradish peroxidase; HRP oxidative coupling; inclusion complexes; polymer-analogous modification

(untitled) - Baekeland, L. H. (J. Ind. Eng. Chem., 1909)

(untitled) - Belhadj Tahar, N.; Savall, A. (Electrochim. Acta, 2009)

(untitled) - Hay, A. S.; Blanchard, H. S.; Endres, G. F.; Eustance, J. W. (J. Am. Chem. Soc., 1959)

(untitled) - Shan, J.; Han, L.; Bai, F.; Cao, S. (Polym. Adv. Technol., 2003)

(untitled) - Wang, J.; Jiang, M.; Lu, F. (J. Electroanal. Chem., 1998)

(untitled) - Mita, N.; Tawaki, S.-i.; Uyama, H.; Kobayashi, S. (Chem. Lett., 2002)

(untitled) - Reihmann, M. H.; Ritter, H. (J. Macromol. Sci., Part A: Pure Appl. Chem., 2002)

(untitled) - Wang, L.; Kobatake, E.; Ikariyama, Y.; Aizawa, M. (J. Polym. Sci., Part A: Polym. Chem., 1993)

(untitled) - Kobayashi, S. (J. Polym. Sci., Part A: Polym. Chem., 1999)

(untitled) - Kobayashi, S.; Higashimura, H. (Prog. Polym. Sci., 2003)

(untitled) - Akkara, J. A.; Senecal, K. J.; Kaplan, D. L. (J. Polym. Sci., Part A: Polym. Chem., 1991)

(untitled) - Ayyagari, M.; Akkara, J. A.; Kaplan, D. L. (Acta Polym., 1996)

(untitled) - Mita, N.; Maruichi, N.; Tonami, H.; Nagahata, R.; Tawaki, S.-i.; Uyama, H.; Kobayashi, S. (Bull. Chem. Soc. Jpn., 2003)

(untitled) - Reihmann, M. H.; Ritter, H. (Macromol. Biosci., 2001)

(untitled) - Mejias, L.; Schollmeyer, D.; Sepulveda-Boza, S.; Ritter, H. (Macromol. Biosci., 2003)

(untitled) - Pang, Y.; Ritter, H.; Tabatabai, M. (Macromolecules, 2003)

(untitled) - Reihmann, M. H.; Ritter, H. (Macromol. Chem. Phys., 2000)

(untitled) - Reihmann, M. H.; Ritter, H. (Macromol. Chem. Phys., 2000)

(untitled) - Mejias, L.; Reihmann, M. H.; Sepulveda-Boza, S.; Ritter, H. (Macromol. Biosci., 2002)

(untitled) - Razumiene, J.; Meškys, R.; Gureviciene, V.; Laurinavicius, V.; Reshetova, M. D.; Ryabov, A. D. (Electrochem. Commun., 2000)

(untitled) - Askarov, I. R.; Kirgizov, S. M.; Nurimdinova, G. T. (Pharm. Chem. J., 1988)

(untitled) - Ho, C.-L.; Wong, W.-Y. (Coord. Chem. Rev., 2011)

(untitled) - Ryabov, A. D.; Kurova, V. S.; Goral, V. N.; Reshetova, M. D.; Razumiene, J.; Simkus, R.; Laurinavičius, V. (Chem. Mater., 1999)

(untitled) - Del Valle, E. M. M. (Process Biochem., 2004)

(untitled) - Szejtli, J. (J. Mater. Chem., 1997)

(untitled) - Godinez, L. A.; Patel, S.; Criss, C. M.; Kaifer, A. E. (J. Phys. Chem., 1995)

(untitled) - Harada, A.; Takahashi, S. (J. Inclusion Phenom. Macrocyclic Chem., 1984)

(untitled) - Luong, J. H. T.; Brown, R. S.; Schmidt, P. M. (J. Mol. Recognit., 1995)

(untitled) - Menger, F. M.; Sherrod, M. J. (J. Am. Chem. Soc., 1988)

(untitled) - Yang, Z.; Breslow, R. (Tetrahedron Lett., 1997)

(untitled) - Nyamori, V. O.; Bala, M. D. (Acta Crystallogr., Sect. E: Struct. Rep. Online, 2008)

(untitled) - Kurioka, H.; Komatsu, I.; Uyama, H.; Kobayashi, S. (Macromol. Rapid Commun., 1994)

(untitled) - Uyama, H.; Kurioka, H.; Sugihara, J.; Kobayashi, S. (Bull. Chem. Soc. Jpn., 1996)